2019
DOI: 10.1101/570929
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tactile sensory channels over-ruled by frequency decoding system that utilizes spike pattern regardless of receptor type

Abstract: 2The established view is that vibrotactile stimuli evoke two qualitatively distinctive cutaneous sensations, 3 flutter (frequencies < 60 Hz) and vibratory hum (frequencies > 60 Hz), subserved by two distinct 4 receptor types (Meissner's and Pacinian corpuscle, respectively) which may engage different neural 5 processing pathways or channels and fulfill quite different biological roles. In psychological and 6 physiological literature those two systems have been labelled as Pacinian and non-Pacinian channels. 7H… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 24 publications
4
12
0
Order By: Relevance
“…These findings are consistent with recent findings from our laboratory which revealed that the spiking pattern, rather than activated afferent type, determined the perceived frequency of repetitive mechanical stimuli [ 16 ]. In that study, we found that low-frequency spike trains in Pacinian (FA2) afferents could induce a vibratory percept, even though Meissner (FA1) afferents had been traditionally thought to be solely responsible for perception of low frequency flutter vibrations (<60 Hz), whereas higher frequency activation of Pacinian (FA2) afferents would evoke a different percept of vibratory hum [ 24 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These findings are consistent with recent findings from our laboratory which revealed that the spiking pattern, rather than activated afferent type, determined the perceived frequency of repetitive mechanical stimuli [ 16 ]. In that study, we found that low-frequency spike trains in Pacinian (FA2) afferents could induce a vibratory percept, even though Meissner (FA1) afferents had been traditionally thought to be solely responsible for perception of low frequency flutter vibrations (<60 Hz), whereas higher frequency activation of Pacinian (FA2) afferents would evoke a different percept of vibratory hum [ 24 ].…”
Section: Discussionsupporting
confidence: 93%
“…While the results in our first experiment, where we used electrical pulses to create bursting trains of the same periodicity but different number of spikes, were best explained by the burst gap code rather than a periodicity or rate code, the mean PSEs were lower than that would be predicted simply from the inter-burst duration. Though the difference in PSEs between electrical and mechanical stimulation was statistically significant, it is unknown whether this difference indicates any physiological importance, as it is well within the Weber fraction of ~0.2–0.3 that has been previously reported in the literature [ 16 , 34 38 ]. One possible explanation for this bias towards lower frequencies may be that electrical stimulation recruits all afferent types non-selectively, so that the slowly adapting (SA) afferents would be recruited in addition to the fast adapting (FA) afferents, whereas the mechanical stimulus predominantly activated FA afferents [ 5 ].…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…invariably reaching a discriminability value of 1), a phenomenon consistent with our notion (and with numerous previous studies) that afferents being temporally local encoders (e.g. Birznieks et al, 2019;Gerdjikov et al, 2010;Stüttgen and Schwarz, 2010). A trivial consequence of measuring responses to single pulses, from neurons devoid of spike adaptation, is that increasing pulse frequency does not affect discriminability.…”
Section: Figs 4dgsupporting
confidence: 91%
“…Third, the increase in the observed pRF size for higher frequencies of vibrotactile stimulation might be an extra-classical receptive field effect (Friston 2005 ; Schwabe et al 2006 ). It has been suggested that vibrotactile frequency discrimination is not solely driven by mechanoreceptive afferents (Kuroki et al 2017 ; Birznieks et al 2019 ). There may be an additional system for vibrotactile frequency processing, possibly involving horizontal connections (Schwark and Jones 1989 ) or the secondary somatosensory cortex (Nelson et al 2004 ; Chung et al 2013 ; Kalberlah et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%